Phenotypic variation and association of agronomic traits in tepary bean genotypes under drought-stress and non-stress conditions - Mwale, Saul Eric; Shimelis, Hussein; Nkhata, Wilson; Sefasi, Abel; Fandika, Isaac; Mashilo, Jacob (Informa UK Limited, 2024)
Genetic variation for economic traits associated with drought adaptation is a prerequisite for developing climate-smart crop varieties, including tepary bean (Phaseolus acutifolius A. Gray). This study aimed to assess the magnitude of genetic variation and the relationship of agronomic traits among 45 tepary bean genotypes under drought-stress (DS) and non-stress (NS) conditions and to identify key traits to aid in the selection of genotypes for drought-tolerance breeding. The study was conducted across three locations in 2019/2020 and 2021/2022 seasons using a 9 × 5 alpha lattice design with two replications. Significant (p < 0.05) genotypic variation was observed for assessed traits under DS and NS conditions. Under DS and NS conditions, seed yield was significantly and positively correlated with the number of pods per plant (NPP) (r = 0.50 and r = 0.57, respectively) and above-ground shoot biomass (r = 0.34 and r = 0.29, respectively). This implied that simultaneous selection for these traits may improve seed yield gains. Highly statistically significant positive direct effects on seed yield were recorded for NPP under both DS and NS conditions. The following genotypes were high yielding and suitable for cultivation in drought-prone environments: G40138, G40042, G40148, G40136, G40150, G40144A, G40066A, G40020, G40022, G40069, G40068, G40063, G40129, G40133 and G40134.